A northern hemispheric climatology of cross-tropopause exchange for the ERA15 time period (1979-1993) - Sprenger, Michael; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Journal of Geophysical Research: Atmospheres, 2003)
ISSN:0148-0227 ISSN:2169-897X